2013
DOI: 10.1073/pnas.1313798111
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin triggers the synaptic incorporation of AMPA receptors in the hippocampus

Abstract: Ghrelin is a peptide mainly produced by the stomach and released into circulation, affecting energy balance and growth hormone release. These effects are guided largely by the expression of the ghrelin receptor growth hormone secretagogue type 1a (GHS-R1a) in the hypothalamus and pituitary. However, GHS-R1a is expressed in other brain regions, including the hippocampus, where its activation enhances memory retention. Herein we explore the molecular mechanism underlying the action of ghrelin on hippocampal-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 61 publications
8
64
0
8
Order By: Relevance
“…This is consistent with a study in healthy older subjects in which serum ghrelin was linked to poorer WM function (85). Ghrelin has also been associated with the synaptic accumulation of the AMPA glutamate receptors and increases in LTP, a form of synaptic plasticity that is thought to underlie learning and memory (86).…”
Section: Resultssupporting
confidence: 90%
“…This is consistent with a study in healthy older subjects in which serum ghrelin was linked to poorer WM function (85). Ghrelin has also been associated with the synaptic accumulation of the AMPA glutamate receptors and increases in LTP, a form of synaptic plasticity that is thought to underlie learning and memory (86).…”
Section: Resultssupporting
confidence: 90%
“…We speculate that CPT1C is a sensor of the energetic status of the neuron through its ability to bind malonyl-CoA (2), an intermediate in the fatty acid synthesis, whose cellular levels in hippocampus fluctuate during fasting and feeding (40). In fact, it has been described that the regulation of energy metabolism contributes to AMPAR synaptic incorporation (41), synaptic plasticity (42,43), and memory processes (44).…”
Section: Cpt1cmentioning
confidence: 99%
“…Furthermore, metabolic hormones such as ghrelin and leptin also contribute to the synaptic incorporation of AMPARs and learning processes. It has been demonstrated that ghrelin increases memory retention in rodents [81], enhances longterm potentiation in the hippocampus [82], and increases the delivery of AMPARs to synapses [83]. In addition, leptin regulates AMPAR trafficking [84] and synaptic plasticity [85].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%